Phase Relationship between Alternans of Early and Late Phases of Ventricular Action Potentials - Jing, Linyuan; Agarwal, Anuj; Chourasia, Sonam; Patwardhan, Abhijit (Frontiers in Physiology, 2012)
Background: Alternans of early phase and of duration of action potential (AP) critically affect dispersion of refractoriness through their influence on conduction and repolarization. We investigated the phase relationship between the two alternans and its effect on conduction. Methods and Results: Transmembrane potentials recorded from ventricles of 8 swine and 3 canines during paced activation intervals of ≤ 300 ms were used to quantify alternans of maximum rate of depolarization (|dv/dt|max) and of APD. Incidence of APD alternans was 62% and 76% in swine and canines. Alternans of APD was frequently accompanied with alternans of |dv/dt|max. Of these, 4 and 26 % were out of phase in swine and canines, i.e. low |dv/dt|max preceded long APD. Computer simulations show that out of phase alternans attenuate variation of wavelength and thus minimize formation of spatially discordant alternans. Conclusions: The spontaneous switching of phase relationship between alternans of depolarization and repolarization suggests that mechanisms underlying these alternans may operate independent of each other. The phase between these alternans can critically impact spatial dispersion of refractoriness and thus stability of conduction, with the in phase relation promoting transition from concord to discord while out of phase preventing formation of discord.